Self-reported foot strike patterns and sonographic evidence of Achilles tendinopathy in asymptomatic marathon runners. Issue 12 (18th June 2022) - Marberry, Scott M.; Filmalter, Sara E.; Pujalte, George G.A.; Presley, James C.; DeMatas, Kristina F.; Montero, Daniel P.; Israni, Krishna; Ball, Colleen T.; Maynard, Jennifer R.
ABSTRACT: It is unknown whether ultrasound findings and symptoms of Achilles tendinopathy in runners correlate with foot strike patterns. We aimed to examine the relationships among Achilles tendon ultrasound findings in runners with or without Achilles tendinopathy, their foot strike patterns, and their training regimens. We recruited marathon runners 18 years of age or older with no history of Achilles tendon pain or surgery participating in the 2018 DONNA Marathon. Participants completed surveys and underwent Achilles tendon sonographic evaluations and were categorized by foot strike patterns. Seventy-nine runners were included; 22 (28%) with forefoot, 30 (38%) midfoot, and 27 (34%) hindfoot strike patterns. Foot strike pattern was not associated with tendon hyperaemia ( P = 1.00) or hypoechogenicity ( P = .97), and there was no association of cross-sectional area of the Achilles tendon with peak weekly distance while training. Sonographic characteristics of Achilles tendinopathy did not correlate with foot strike patterns or training regimens. Although not statistically significant, it is worth noting that cross-sectional area was 1 mm 2 larger per every 1 kg/m 2 increase in body mass index.